Trolls : an Unnatural History. - Lindow, John (Reaktion Books, 2014)
Trolls lurk under bridges waiting to eat children, threaten hobbits in Middle-Earth, and invade the dungeons of Hogwarts. Often they are depicted as stupid, slow, and ugly creatures, but they also appear as comforting characters in some children's stories or as plastic dolls with bright, fuzzy hair. Today, the name of this fantastic being from Scandinavia has found a wider reach: it is the word for the homeless in California and slang for the antagonizing and sometimes cruel people on the Internet. But how did trolls go from folktales to the World Wide Web? To explain why trolls still hold our.